Polyolefin-based adhesive composition

JP7632499B2Active Publication Date: 2025-02-19TOYOBO MC CORP
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
JP2023014472
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-05-29
Filing Date
2023-02-02
Publication Date
2025-02-19
Estimated Expiration
2038-04-12

AI Technical Summary

Benefits of technology

【0016】 本発明にかかる接着剤組成物は、酸変性ポリオレフィン、多官能ポリイソシアネート硬化剤、および有機溶剤を含有し、長期間保存しても増粘やゲル化を生じることなく良好なポットライフ性を維持することができる。さらにポリオレフィン基材の熱収縮影響が小さい120℃以下のような低温で張り合わせ、40℃以下のような低温でのエージングを行ってもポリオレフィン樹脂基材と金属基材との良好な接着性、耐薬品性さらに成形性を両立することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632499000001
    Figure 0007632499000001
  • Figure 0007632499000002
    Figure 0007632499000002
  • Figure 0007632499000003
    Figure 0007632499000003
Patent Text Reader

Abstract

The present invention provides an adhesive composition containing an acid-modified polyolefin and a multifunctional polyisocyanate curing agent, which has a good pot life, and which exhibits good adhesion between metal substrates and polyolefin resin substrates, chemical resistance, and moldability. [Solution] An adhesive composition containing an acid-modified polyolefin (A), a multifunctional polyisocyanate curing agent (B), and an organic solvent (C), wherein the acid-modified polyolefin (A) has an acid value of 2 to 50 mg KOH / g-resin and an acetone extractable component ratio of 0.01 to 2 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition that exhibits good adhesion between a polyolefin resin substrate and a metal substrate, chemical resistance, and moldability. More specifically, the present invention relates to an adhesive composition that contains an acid-modified polyolefin, a multifunctional polyisocyanate curing agent, and an organic solvent. In particular, the present invention relates to an adhesive composition for lithium ion batteries (hereinafter abbreviated as LiB), and a packaging material that is a laminate containing the same. [Background technology]

[0002] In recent years, LiBs that can be made ultra-thin and compact have been actively developed as batteries for use in personal computers, mobile terminal devices such as mobile phones, video cameras, satellites, etc. Unlike the metal cans that have been used conventionally, the packaging materials for these LiBs have come to use laminates with a structure such as a base layer / barrier layer / sealant layer, due to their advantages of being lightweight and allowing the shape of the battery to be freely selected.

[0003] LiB contains, as the battery contents, a cathode material and an anode material, as well as an electrolyte solution in which a lithium salt is dissolved in an aprotic solvent such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate, or an electrolyte layer made of a polymer gel impregnated with the electrolyte solution. If such a highly penetrating solvent passes through the sealant layer, it reduces the laminate strength between the barrier layer and the sealant layer, causing delamination, and ultimately causing the electrolyte to leak. In addition, materials such as LiPF6 and LiBF4 are used as lithium salts, which are the electrolyte of batteries, but these salts generate hydrofluoric acid by hydrolysis reaction with moisture, and the hydrofluoric acid corrodes the barrier layer, thereby reducing the laminate strength. It is necessary for battery packaging materials to have resistance to electrolytes in this way.

[0004] LiBs are also expected to be used in a variety of environments, and so they need to have more severe resistance. For example, when used in mobile devices, they need to be leak-resistant in high-temperature environments of 60 to 70 degrees Celsius, such as inside a car. They also need to be water-resistant to prevent moisture from seeping in when used in a mobile phone and accidentally dropped in water.

[0005] Under these circumstances, various packaging materials for lithium batteries with improved electrolyte resistance have been proposed (see, for example, Patent Documents 1 to 3).

[0006] Furthermore, in the battery packaging material, when the battery element is enclosed, the material is molded in a mold to form a space for accommodating the battery element. During this molding, the battery packaging material is stretched, which causes a problem that cracks and pinholes are likely to occur in the barrier layer at the flange of the mold. In particular, with the recent demand for smaller and thinner batteries, thinner battery packaging materials are required, and such problems are more likely to occur.

[0007] Under these circumstances, battery packaging materials with improved moldability have been proposed (see, for example, Patent Documents 4 and 5). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2001-243928 A [Patent Document 2] JP 2004-42477 A [Patent Document 3] JP 2009-238475 A [Patent Document 4] JP 2002-216714 A [Patent Document 5] JP 2003-31188 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, the above-mentioned proposed packaging materials for lithium batteries are still insufficient in terms of electrolyte resistance and moldability, and even if the electrolyte resistance and moldability are greatly improved, problems remain. Specifically, it is difficult to ensure both the pot life of the adhesive after the hardener is mixed and the electrolyte resistance (Patent Document 1), the lamination machine is restricted because the adhesion is performed by extrusion lamination, and the polyolefin substrate is affected by heat shrinkage due to lamination at high temperatures (Patent Document 2), and the drying time is long because the polyolefin base material is water-based, limiting the production conditions (Patent Document 3). In addition, a process of coating the surface of the outer layer film with an amide-based slip agent must be provided, which reduces productivity, and the laminate strength between the outer layer film and the aluminum foil cannot be obtained sufficiently due to the coated amide-based slip agent (Patent Document 4). Since only an unstretched polypropylene resin film is arranged on the inner layer side of the aluminum foil, or only a film of a blended resin of polypropylene and polyethylene is arranged on the inner layer side of the aluminum foil, pinholes are generated in the aluminum foil when it is molded into a rectangular parallelepiped shape, or breaks (cracks) are easily generated in the aluminum foil, and sufficient moldability cannot be obtained (Patent Document 5).

[0010] The present invention aims to provide an adhesive composition that is excellent in adhesion, chemical resistance (electrolyte resistance) and moldability without problems such as pot life and restrictions on production conditions, and further to provide a battery packaging material including an adhesive layer made of the adhesive composition, and a battery using the packaging material. [Means for solving the problem]

[0011] In order to achieve the above object, the present inventors have intensively studied and found that it is effective to provide a layer that can sufficiently follow the elongation during molding not only on the outer layer side but also on the inner layer side of the aluminum foil, and have come to propose the following invention.

[0012] An adhesive composition comprising an acid-modified polyolefin (A), a multifunctional polyisocyanate curing agent (B) and an organic solvent (C), wherein the acid-modified polyolefin (A) has an acid value of 2 to 50 mg KOH / g-resin and an acetone extractable component ratio of 0.01 to 2 mass%.

[0013] It is preferable that the composition contains 0.5 to 40 parts by mass of a polyfunctional polyisocyanate curing agent (B) and 80 to 2000 parts by mass of an organic solvent (C) relative to 100 parts by mass of the acid-modified polyolefin (A). It is also preferable that the organic solvent (C) is a mixed liquid of a solvent (C1) and a solvent (C2), the solvent (C1) being one or more solvents selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, and halogenated hydrocarbons, the solvent (C2) being one or more solvents selected from the group consisting of alcohol-based solvents, ketone-based solvents, ester-based solvents, and glycol ether-based solvents, and the solvent (C1) / solvent (C2) is 50 to 97 / 50 to 3 (mass ratio).

[0014] The adhesive composition is preferably used for bonding a polyolefin resin substrate to a metal substrate.

[0015] A laminate of a polyolefin resin substrate and a metal substrate bonded with the adhesive composition, and a packaging material for lithium ion batteries comprising the laminate as a constituent member. Effect of the Invention

[0016] The adhesive composition according to the present invention contains an acid-modified polyolefin, a multifunctional polyisocyanate curing agent, and an organic solvent, and can maintain a good pot life without thickening or gelling even when stored for a long period of time. Furthermore, even when the composition is bonded at a low temperature of 120°C or less, where the thermal shrinkage effect of the polyolefin substrate is small, and aged at a low temperature of 40°C or less, it is possible to achieve good adhesion between the polyolefin resin substrate and the metal substrate, chemical resistance, and moldability.

[0017] According to the present invention, the adhesive layer can be sufficiently cured by the aging process after lamination while maintaining a good pot life, and excellent adhesion and chemical resistance can be exhibited. Furthermore, it is possible to obtain an adhesive layer that satisfies the storage modulus and breaking elongation required for exhibiting excellent moldability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described in detail.

[0019] <Acid-modified polyolefin (A)> The acid-modified polyolefin (A) used in the present invention is an acid-modified polyolefin having an acid value of 2 to 50 mg KOH / g-resin and an acetone extractable component ratio of 0.01 to 2 mass %.

[0020] The acid-modified polyolefin (A) used in the present invention is not limited, but is preferably one obtained by grafting at least one of polyethylene, polypropylene, and propylene-α-olefin copolymer with at least one of α,β-unsaturated carboxylic acid and its acid anhydride.

[0021] Propylene-α-olefin copolymer is a copolymer of propylene as a main component with α-olefin. As the α-olefin, for example, one or more of ethylene, 1-butene, 1-heptene, 1-octene, 4-methyl-1-pentene, vinyl acetate, etc. can be used. Among these α-olefins, ethylene and 1-butene are preferred. The ratio of the propylene component to the α-olefin component in the propylene-α-olefin copolymer is not limited, but the propylene component is preferably 50 mol% or more, more preferably 70 mol% or more.

[0022] Examples of at least one of α,β-unsaturated carboxylic acids and their acid anhydrides include maleic acid, itaconic acid, citraconic acid, and their acid anhydrides. Among these, acid anhydrides are preferred, and maleic anhydride is more preferred. Specifically, maleic anhydride-modified polypropylene, maleic anhydride-modified propylene-ethylene copolymer, maleic anhydride-modified propylene-butene copolymer, maleic anhydride-modified propylene-ethylene-butene copolymer, etc. can be mentioned, and these acid-modified polyolefins can be used alone or in combination of two or more.

[0023] The acid value of the acid-modified polyolefin (A) must be in the range of 2 to 50 mgKOH / g-resin from the viewpoint of adhesion between the polyolefin resin substrate and the metal substrate and resistance to electrolyte. It is preferably in the range of 3 to 45 mgKOH / g-resin, more preferably 5 to 40 mgKOH / g-resin, and particularly preferably 7 to 35 mgKOH / g-resin. If it is less than the above value, the compatibility with the curing agent may be poor. Therefore, the crosslinking density may be low, and the adhesive strength and chemical resistance (resistance to electrolyte) may be reduced. If it exceeds the above value, the molecular weight is low and the cohesive force is weak, and the adhesive strength and chemical resistance (resistance to electrolyte) may be reduced. Furthermore, the production efficiency is also reduced, which is not preferable.

[0024] The acid value of the acid-modified polyolefin (A) can be adjusted by the amounts of the α,β-unsaturated carboxylic acid, the acid anhydride of the α,β-unsaturated carboxylic acid, and the radical generator used.

[0025] The acetone extractable component ratio of the acid-modified polyolefin (A) must be in the range of 0.01% by mass to 2% by mass from the viewpoint of adhesion between the polyolefin resin substrate and the metal substrate and resistance to electrolyte. It is preferably 0.03% by mass to 1.7% by mass, more preferably 0.05% by mass to 1.4% by mass, even more preferably 0.07% by mass to 1.2% by mass, and particularly preferably 0.1% by mass to 1% by mass. If it is less than the above value, the production efficiency decreases, which is not preferable. If it exceeds the above value, the cohesive force may be weakened, resulting in poor adhesion, chemical resistance, and moldability.

[0026] The storage modulus (E') of the acid-modified polyolefin (A) at 25°C is preferably in the range of 10 to 2000 MPa from the viewpoint of adhesion between the polyolefin resin substrate and the metal substrate and chemical resistance (electrolyte resistance). More preferably, it is 15 to 1700 MPa, even more preferably 20 to 1400 MPa, particularly preferably 25 to 1100 MPa, and most preferably 30 to 800 MPa. If it is less than the above value, the adhesive layer made of the adhesive composition may have insufficient cohesive force, and the adhesiveness and chemical resistance (electrolyte resistance) may be poor. If it exceeds the above value, the conformability of the adhesive layer made of the adhesive composition may decrease, and the adhesiveness may be poor. In addition, if it is within the above range, the adhesiveness and substrate conformability are improved, and even the moldability of the laminate is improved, making it more preferable as a packaging material for lithium-ion batteries.

[0027] The tensile elongation at break (Eb) of the acid-modified polyolefin (A) at 25°C is preferably in the range of 50% to 1000%. More preferably, it is 80% to 900%, even more preferably, it is 120% to 800%, particularly preferably, it is 160% to 700%, and most preferably, it is 200% to 600%. If it is less than the above value, the conformability of the adhesive layer made of the adhesive composition decreases, which may lead to pinholes during molding and poor moldability. In addition, the tensile elongation at break (Eb) and the storage modulus (E') are generally contradictory properties, and if it exceeds the above value, the storage modulus (E') decreases, and the adhesiveness and electrolyte resistance may be poor. In addition, if it is within the above range, the adhesiveness and substrate conformability are improved, and the moldability of the laminate is also improved, making it more preferable as a packaging material for lithium-ion batteries.

[0028] The weight average molecular weight (Mw) of the acid-modified polyolefin (A) is preferably in the range of 10,000 to 200,000. More preferably, it is in the range of 20,000 to 180,000, even more preferably, it is in the range of 30,000 to 160,000, particularly preferably, it is in the range of 40,000 to 140,000, and most preferably, it is in the range of 50,000 to 110,000. If it is less than the above value, the cohesive force may be weak and the adhesiveness may be poor. On the other hand, if it exceeds the above value, the fluidity may be low and problems may occur in the operability during adhesion. If it is within the above range, it is preferable because the curing reaction with the curing agent is utilized.

[0029] The crystallinity of the acid-modified polyolefin (A) refers to the fact that a clear melting peak is shown during the temperature rise from -100°C to 250°C at 20°C / min using a differential scanning calorimeter (DSC).

[0030] By making the acid-modified polyolefin crystalline, it is advantageous to have stronger cohesive strength and better adhesiveness and chemical resistance than amorphous polyolefins.

[0031] The melting point (Tm) of the acid-modified polyolefin (A) is preferably in the range of 50°C to 120°C, more preferably in the range of 60°C to 100°C, and most preferably in the range of 70°C to 90°C. If it is less than the above value, the cohesive force derived from the crystals may be weak, and the adhesiveness and chemical resistance may be poor. On the other hand, if it exceeds the above value, the solution stability and fluidity may be low, and problems may occur in operability during adhesion.

[0032] The heat of fusion (ΔH) of the acid-modified polyolefin (A) is preferably in the range of 1 J / g to 60 J / g. More preferably, it is in the range of 3 J / g to 50 J / g, and most preferably, it is in the range of 5 J / g to 40 J / g. If it is less than the above value, the cohesive force derived from the crystals may be weak, and the adhesiveness and chemical resistance may be poor. On the other hand, if it exceeds the above value, the solution stability and fluidity may be low, and problems may occur in operability during adhesion.

[0033] The method for producing the acid-modified polyolefin (A) is not particularly limited, and examples thereof include a radical graft reaction (i.e., a reaction in which radical species are generated on a polymer that is to become the main chain, and an unsaturated carboxylic acid and an acid anhydride are graft polymerized using the radical species as a polymerization initiation point).

[0034] As the radical generator, although not particularly limited, it is preferable to use an organic peroxide.As the organic peroxide, although not particularly limited, peroxides such as di-tert-butyl peroxyphthalate, tert-butyl hydroperoxide, dicumyl peroxide, benzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, methyl ethyl ketone peroxide, di-tert-butyl peroxide, lauroyl peroxide, etc.; azonitriles such as azobisisobutyronitrile, azobisisopropionitrile, etc. can be mentioned.

[0035] <Multifunctional polyisocyanate curing agent (B)> The polyfunctional polyisocyanate curing agent (B) used in the present invention is not particularly limited as long as it is a polyisocyanate having two or more isocyanate groups in one molecule, and well-known diisocyanates and compounds derived therefrom can be preferably used. Examples of the diisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, bis(4-isocyanatocyclohexyl)methane, and hydrogenated diphenylmethane diisocyanate. In addition, compounds derived from the diisocyanates, that is, isocyanurate bodies, adduct bodies, biuret types, uretdione bodies, allophanate bodies, prepolymers having isocyanate residues (low polymers obtained from diisocyanates and polyols), and complexes thereof, etc. These may be used alone or in any combination of two or more.

[0036] Furthermore, a compound obtained by reacting a part of the isocyanate groups of the above isocyanate compound with a compound having reactivity with the isocyanate group may be used as a polyfunctional isocyanate curing agent. Examples of compounds reactive with an isocyanate group include compounds containing an amino group, such as butylamine, hexylamine, octylamine, 2-ethylhexylamine, dibutylamine, ethylenediamine, benzylamine, and aniline; compounds containing a hydroxyl group, such as methanol, ethanol, propanol, isopropanol, butanol, hexanol, octanol, 2-ethylhexyl alcohol, dodecyl alcohol, ethylene glycol, propylene glycol, benzyl alcohol, and phenol; compounds having an epoxy group, such as allyl glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and cyclohexanedimethanol diglycidyl ether; and compounds containing a carboxylic acid, such as acetic acid, butanoic acid, hexanoic acid, octanoic acid, succinic acid, adipic acid, sebacic acid, and phthalic acid.

[0037] As the polyfunctional polyisocyanate curing agent (B) used in the present invention, those having an isocyanurate of the above diisocyanate are preferable because they have excellent resistance to electrolyte.

[0038] The amount of the polyfunctional polyisocyanate curing agent (B) used in the present invention is preferably in the range of 0.5 to 40 parts by mass, more preferably 1 to 35 parts by mass, even more preferably 2 to 30 parts by mass, and particularly preferably 3 to 25 parts by mass, relative to 100 parts by mass of the acid-modified polyolefin (A). If it is less than the above value, sufficient curing effect may not be obtained, and adhesion and chemical resistance may be low. If it exceeds the above range, pot life and adhesion may decrease, and pinholes may occur during molding due to decreased followability. Furthermore, it is not preferable from the viewpoint of cost.

[0039] <Organic solvent (C)> The organic solvent (C) used in the present invention is not particularly limited as long as it dissolves the acid-modified polyolefin (A) and the polyfunctional polyisocyanate curing agent (B).Specific examples of the organic solvent include aromatic hydrocarbons such as benzene, toluene, and xylene, aliphatic hydrocarbons such as hexane, heptane, octane, and decane, alicyclic hydrocarbons such as cyclohexane, cyclohexene, methylcyclohexane, and ethylcyclohexane, halogenated hydrocarbons such as trichloroethylene, dichloroethylene, chlorobenzene, and chloroform, alcohol solvents such as methanol, ethanol, isopropyl alcohol, butanol, pentanol, hexanol, propanediol, and phenol, and ketones such as acetone, methyl isobutyl ketone, methyl ethyl ketone, pentanone, hexanone, cyclohexanone, isophorone, and acetophenone. Examples of solvents that can be used include cellosolves such as methyl cellosolve and ethyl cellosolve, ester solvents such as methyl acetate, ethyl acetate, butyl acetate, methyl propionate and butyl formate, and glycol ether solvents such as ethylene glycol mono-n-butyl ether, ethylene glycol mono-iso-butyl ether, ethylene glycol mono-tert-butyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol mono-iso-butyl ether, triethylene glycol mono-n-butyl ether and tetraethylene glycol mono-n-butyl ether, and these can be used alone or in combination of two or more.

[0040] The organic solvent (C) is preferably in the range of 80 to 2000 parts by mass relative to 100 parts by mass of the acid-modified polyolefin (A), more preferably 90 to 1600 parts by mass, even more preferably 100 to 1200 parts by mass, and particularly preferably 110 to 800 parts by mass. If it is less than the above range, the solution state and pot life may be deteriorated, and if it exceeds the above range, it may be disadvantageous in terms of productivity, production cost, and transportation cost of the laminate and the LiB packaging material containing the laminate.

[0041] From the viewpoint of the solution state and pot life of the adhesive composition, the organic solvent (C) is preferably a mixture of one or more solvents (C1) selected from the group consisting of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, and halogenated hydrocarbons, and one or more solvents (C2) selected from the group consisting of alcohol-based solvents, ketone-based solvents, ester-based solvents, and glycol ether-based solvents. The mixing ratio is preferably in the range of solvent (C1) / solvent (C2)=50-97 / 50-3 (mass ratio), more preferably 55-95 / 45-5 (mass ratio), even more preferably 60-90 / 40-10 (mass ratio), and particularly preferably 70-80 / 30-20 (mass ratio). If it is out of the above range, the solution state and pot life of the adhesive composition may be deteriorated. In addition, it is particularly preferable that the solvent (C1) is an aromatic hydrocarbon or an alicyclic hydrocarbon, and the solvent (C2) is a ketone-based solvent.

[0042] <Adhesive composition> The adhesive composition according to the present invention is a mixture of the acid-modified polyolefin (A), the polyfunctional polyisocyanate curing agent (B) and the organic solvent (C), and the acid-modified polyolefin (A) and the curing agent (B) may be dissolved or dispersed in the organic solvent (C). From the viewpoint of pot life, it is preferable that they are dissolved.

[0043] In the adhesive composition according to the present invention, various tackifiers, thermoplastic elastomers, and plasticizers can be blended in addition to the acid-modified polyolefin (A), the polyfunctional polyisocyanate curing agent (B), and the organic solvent (C) within the range that does not impair the performance of the present invention. Examples of the tackifier include, but are not limited to, polyterpene resins, rosin resins, aliphatic petroleum resins, alicyclic petroleum resins, copolymerized petroleum resins, and hydrogenated petroleum resins. Examples of the thermoplastic elastomer include styrene-ethylene-butylene-styrene copolymer resins, styrene-ethylene-propylene-styrene and other styrene-based elastomers, ethylene-propylene copolymer resins, ethylene-butene copolymer resins, ethylene-vinyl acetate copolymer resins, ethylene-ethyl acrylate copolymer resins, and other olefin-based elastomers. Examples of the plasticizer include liquid rubbers such as polyisoprene and polybutene, and process oils. These tackifiers, thermoplastic elastomers, and plasticizers may be used alone or in combination of two or more.

[0044] In the adhesive composition according to the present invention, various curing agents can be used in combination with the acid-modified polyolefin (A), the polyfunctional polyisocyanate curing agent (B) and the organic solvent (C) as long as the performance of the present invention is not impaired. The curing agent is not particularly limited, but examples thereof include epoxy resins, carbodiimide compounds, oxazoline compounds, coupling agents, and the like. Examples of the epoxy resin include glycidyl ester types such as hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester, triglycidyl isocyanurate, 3,4-epoxycyclohexylmethylcarboxylate, epoxidized polybutadiene, alicyclic or aliphatic epoxides such as epoxidized soybean oil, glycidyl ether type epoxy resins, and glycidyl amine type epoxy resins. Examples of the carbodiimide compound include monocarbodiimide compounds such as dimethylcarbodiimide, diisopropylcarbodiimide, dicyclohexylcarbodiimide, t-butylisopropylcarbodiimide, diphenylcarbodiimide, and di-β-naphthylcarbodiimide, and polycarbodiimide compounds which can be produced by carrying out a decarboxylation condensation reaction of an organic diisocyanate such as an aliphatic diisocyanate, an aromatic diisocyanate, or an alicyclic diisocyanate in the presence of a condensation catalyst in the absence of a solvent or in an inert solvent. Examples of the oxazoline compound include monooxazoline compounds such as 2-oxazoline, 2-methyl-2-oxazoline, 2-phenyl-2-oxazoline, 2,5-dimethyl-2-oxazoline, and 2,4-diphenyl-2-oxazoline, and dioxazoline compounds such as 2,2'-(1,3-phenylene)-bis(2-oxazoline), 2,2'-(1,2-ethylene)-bis(2-oxazoline), 2,2'-(1,4-butylene)-bis(2-oxazoline), and 2,2'-(1,4-phenylene)-bis(2-oxazoline). Examples of the coupling agent include silane coupling agents and titanate coupling agents.

[0045] The adhesive composition according to the present invention can be used by blending a curing accelerator in addition to the acid-modified polyolefin (A), the polyfunctional polyisocyanate curing agent (B) and the organic solvent (C) within a range that does not impair the performance of the present invention. The curing accelerator is not particularly limited, but examples thereof include metal carboxylates, tertiary amines, quaternary ammonium salts, organic peroxides, hydrazine compounds, metal chelate compounds, phosphorus-containing compounds, basic vulcanizing agents, etc. Examples of the metal carboxylates include metal salts of carboxylic acids having 1 to 30 carbon atoms. Examples of the carboxylic acid constituting the carboxylate metal salt include aliphatic carboxylic acids such as acetic acid, butyric acid, octanoic acid, decanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, behenic acid, octenoic acid, erucic acid, elaidic acid, adipic acid, malonic acid, succinic acid, glutaric acid, citric acid, tartaric acid, malic acid, and diglycolic acid; aromatic carboxylic acids such as benzoic acid, chlorobenzoic acid, anisic acid, aminobenzoic acid, phthalic acid, terephthalic acid, naphthoic acid, naphthalenedicarboxylic acid, and benzenetricarboxylic acid; naphthenic acid; acetone acid, etc. Examples of the metal constituting the carboxylate metal salt include Li, Na, K, Mg, Ca, Zn, Al, Cu, Pb, Co, Fe, Mn, Sn, and Ti.Specific examples of the metal carboxylate include lithium acetate, sodium acetate, magnesium acetate, aluminum acetate, potassium butyrate, calcium butyrate, zinc butyrate, sodium octanoate, calcium octanoate, potassium decanoate, magnesium decanoate, zinc decanoate, lithium laurate, sodium laurate, calcium laurate, aluminum laurate, potassium myristate, sodium myristate, aluminum myristate, sodium palmitate, zinc palmitate, magnesium palmitate, sodium stearate, potassium stearate, calcium stearate, and stearic acid. Examples of the suitable oleic acid salts include zinc, sodium oleate, sodium behenate, sodium benzoate, zinc benzoate, sodium phthalate, aluminum phthalate, magnesium terephthalate, calcium naphthalenedicarboxylate, dibutyltin laurate, tributyltin laurate, dioctyltin laurate, tributyltin acetate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin 2-ethylhexoate, tetrabutyl titanate, tetraisobutyl titanate, tetra 2-ethylhexyl titanate, cobalt naphthenate, copper naphthenate, magnesium naphthenate, and cobalt acetoacetate. Among these, preferred are lithium laurate, sodium laurate, calcium laurate, aluminum laurate, potassium myristate, sodium myristate, aluminum myristate, sodium palmitate, zinc palmitate, magnesium palmitate, sodium stearate, potassium stearate, calcium stearate, zinc stearate, and sodium oleate. In addition, as the metal salt of carboxylic acid, a polymer having a metal salt structure of carboxylic acid can be used. Such polymers include those having a structure in which ethylene and a radical polymerizable carboxylic acid salt of a metal of Group IA, Group IIA, Group IIB, or Group IIIB (e.g., Li, Na, K, Mg, Ca, Zn, Al, etc.) are copolymerized; and those having a structure in which ethylene and a metal salt of a radical polymerizable carboxylic acid and another radical polymerizable carboxylic acid and / or its derivative are multi-component copolymerized.Examples of the tertiary amines include dimethylaniline, triethanolamine, and dimethyl-p-toluidine. Examples of the hydrazine compounds include 1-acetyl-2-phenylhydrazine. Examples of the metal chelate compounds include vanadium acetylacetonate. Examples of the phosphorus-containing compounds include dimethylphosphine and triphenylphosphine. Examples of the basic vulcanizing agents include hexamethylenetetramine and n-butylaldehyde-aniline condensates.

[0046] The adhesive composition of the present invention may contain various additives in addition to the acid-modified polyolefin (A), the polyfunctional polyisocyanate curing agent (B) and the organic solvent (C) within the range that does not impair the performance of the present invention. The additives are not particularly limited, but it is preferable to use a flame retardant, a pigment, an antiblocking agent, etc.

[0047] <Laminate> The laminate of the present invention is obtained by laminating a polyolefin resin substrate and a metal substrate with the adhesive composition of the present invention.

[0048] The lamination method can utilize a conventionally known laminate manufacturing technique. For example, although not particularly limited, the adhesive composition is applied to the surface of the metal substrate using a suitable application means such as a roll coater or a bar coater, and then dried. After drying, while the layer of the adhesive composition (adhesive layer) formed on the surface of the metal substrate is in a molten state, a polyolefin resin substrate is laminated and bonded (laminated) to the applied surface to obtain a laminate. The thickness of the adhesive layer formed from the adhesive composition is not particularly limited, but is preferably 0.5 to 10 μm, more preferably 0.8 to 9.5 μm, and even more preferably 1 to 9 μm.

[0049] <Polyolefin resin substrate> The polyolefin resin substrate may be appropriately selected from conventionally known polyolefin resins. For example, polyethylene, polypropylene, ethylene-propylene copolymer, etc. may be used, but are not particularly limited thereto. Among them, it is preferable to use a non-oriented polypropylene film (hereinafter also referred to as CPP). The thickness is not particularly limited, but is preferably 20 to 100 μm, more preferably 25 to 95 μm, and even more preferably 30 to 90 μm. Note that the polyolefin resin substrate may be blended with pigments or various additives as necessary, or may be subjected to a surface treatment.

[0050] <Metal base material> The metal substrate is not particularly limited, and may be, for example, various metals and alloys thereof, such as aluminum, copper, steel, chromium, zinc, duralumin, and die-casting. The shape of the substrate may be any shape, such as metal foil, rolled steel plate, panel, pipe, can, cap, etc. In general, aluminum foil is preferred from the viewpoint of workability. Although it may vary depending on the purpose of use, it is generally used in the form of a sheet having a thickness of 0.01 to 10 mm, preferably 0.02 to 5 mm. The surfaces of these metal substrates may be either previously treated or left untreated, with the same effects being achieved in either case.

[0051] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the examples. In the examples and comparative examples, parts simply indicate parts by mass. However, Examples 12, 14, 15, 17 and 19 are all reference examples.

[0052] <Production Example of Acid-Modified Polyolefin (A)> Manufacturing Example 1 In a 1L autoclave, 100 parts by mass of propylene-ethylene copolymer (storage modulus at 25°C: 320 MPa, tensile elongation at break at 25°C: 760%), 233 parts by mass of toluene, 1 part by mass of maleic anhydride, and 0.5 parts by mass of di-tert-butyl peroxide were added, and the mixture was heated to 140°C and further stirred for 1 hour (herein referred to as "reacted" for 1 hour). After that, the obtained reaction liquid was cooled to 100°C, and poured into a container containing 717 parts by mass of toluene and 950 parts by mass of methyl ethyl ketone, which had been preheated to 40°C, while stirring, cooled to 40°C, further stirred for 30 minutes, and further cooled to 25°C to precipitate a resin (herein, the operation of pouring the reaction liquid into a solvent such as methyl ethyl ketone while stirring and precipitating a resin by cooling is referred to as "reprecipitation"). Thereafter, the slurry containing the resin was centrifuged to separate the acid-modified propylene-ethylene copolymer graft-polymerized with maleic anhydride, (poly)maleic anhydride, and low molecular weight substances. Furthermore, the acid-modified propylene-ethylene copolymer extracted by centrifugation was added to a container containing 2000 parts by mass of methyl ethyl ketone that had been kept at 25°C in advance, while stirring, and the mixture was stirred for 1 hour. The slurry was then centrifuged to further separate the acid-modified propylene-ethylene copolymer from the (poly)maleic anhydride and low molecular weight substances. This operation was repeated twice for purification (here, the operation of strengthening purification by adding the acid-modified propylene-ethylene copolymer extracted by centrifugation to methyl ethyl ketone while stirring and centrifuging again is referred to as "reslurry"). After purification, the mixture was dried under reduced pressure at 70°C for 5 hours to obtain an acid-modified polyolefin, maleic anhydride-modified propylene-ethylene copolymer (PO-1, acid value 2 mg KOH / g-resin, acetone extractable component ratio 0.1 mass%, storage modulus at 25°C 300 MPa, tensile break elongation at 25°C 600%, weight average molecular weight 190,000, Tm 88°C, △H 37 J / g).

[0053] Manufacturing Example 2 The same procedure as in Production Example 1 was followed except that the amount of maleic anhydride added was changed to 3 parts by mass, the number of reslurries was changed to 1, and the amount of methyl ethyl ketone added during the reslurry was changed to 1,000 parts by mass, to obtain an acid-modified polyolefin, maleic anhydride-modified propylene-ethylene copolymer (PO-2, acid value 5 mg KOH / g-resin, acetone extractable component ratio 1.8 mass%, storage modulus at 25°C 280 MPa, tensile break elongation at 25°C 650%, weight average molecular weight 180,000, Tm 88°C, △H 36 J / g).

[0054] Production Example 3 The same procedures as in Production Example 1 were carried out except that the amount of toluene charged was 150 parts by mass, the amount of maleic anhydride charged was 40 parts by mass, the amount of di-tert-butyl peroxide charged was 8 parts by mass, the reaction time was 3 hours, the solvent used for reprecipitation was 700 parts by mass of methyl ethyl ketone, and the number of reslurries was 5, thereby obtaining an acid-modified polyolefin, a maleic anhydride-modified propylene-ethylene copolymer (PO-3, acid value 48 mg KOH / g-resin, acetone extractable component ratio 0.1 mass%, storage modulus at 25°C 180 MPa, tensile break elongation at 25°C 350%, weight average molecular weight 31,000, Tm 85°C, △H 31 J / g).

[0055] Production Example 4 The same procedures as in Production Example 1 were carried out except that the amount of toluene was changed to 150 parts by mass, the amount of maleic anhydride was changed to 40 parts by mass, the amount of di-tert-butyl peroxide was changed to 8 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurries was changed to 3, to obtain an acid-modified polyolefin, maleic anhydride-modified propylene-ethylene copolymer (PO-4, acid value 48 mg KOH / g-resin, acetone extractable component ratio 1.8 mass%, storage modulus at 25°C 150 MPa, tensile elongation at break 300% at 25°C, weight average molecular weight 27,000, Tm 85°C, △H 30 J / g).

[0056] Production Example 5 The same procedures as in Production Example 1 were carried out except that the amount of toluene charged was 150 parts by mass, the amount of maleic anhydride charged was 20 parts by mass, the amount of di-tert-butyl peroxide charged was 6 parts by mass, the reaction time was 3 hours, the solvent used for reprecipitation was 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was 1000 parts by mass of methyl ethyl ketone, and the number of reslurries was 2, to obtain an acid-modified polyolefin, maleic anhydride-modified propylene-ethylene copolymer (PO-5, acid value 25 mg KOH / g-resin, acetone extractable component ratio 0.9 mass%, storage modulus at 25°C 400 MPa, tensile elongation at break 500% at 25°C, weight average molecular weight 60,000, Tm 87°C, △H 35 J / g).

[0057] Production Example 6 A maleic anhydride-modified propylene-ethylene copolymer (PO-6, acid value 25 mg KOH / g-resin, acetone extractable component ratio 1.0 mass%, storage modulus at 25 ° C. 52 MPa, tensile elongation at break 1050% at 25 ° C.) was obtained as in Production Example 1, except that 100 parts by mass of propylene-ethylene copolymer, 150 parts by mass of toluene, 30 parts by mass of maleic anhydride, 6 parts by mass of di-tert-butyl peroxide, reaction time 3 hours, solvent used for reprecipitation 700 parts by mass of methyl ethyl ketone, solvent used for reslurry 1000 parts by mass of methyl ethyl ketone, and number of reslurries was changed to 2.

[0058] Production Example 7 A maleic anhydride-modified propylene homopolymer (PO-7, acid value 25 mg KOH / g-resin, acetone extractable component ratio 0.9 mass%, storage modulus at 25 ° C. 2100 MPa, tensile elongation at break at 25 ° C. 900%) was obtained as an acid-modified polyolefin by the same procedure as in Production Example 1, except that 100 parts by mass of propylene homopolymer (storage modulus at 25 ° C. 2100 MPa, tensile elongation at break at 25 ° C. 900%), 150 parts by mass of toluene, 30 parts by mass of maleic anhydride, 6 parts by mass of di-tert-butyl peroxide, reaction time 3 hours, solvent used for reprecipitation 700 parts by mass of methyl ethyl ketone, solvent used for reslurry 1000 parts by mass of methyl ethyl ketone, and the number of reslurries was changed to 2.

[0059] Production Example 8 A maleic anhydride-modified propylene-ethylene copolymer (PO-8, acid value 25 mg KOH / g-resin, acetone extractable component ratio 1.0 mass%, storage modulus at 25 ° C. 2720 MPa, tensile elongation at break 400% at 25 ° C.) was used as 100 parts by mass, toluene was charged at 186 parts by mass, maleic anhydride was charged at 20 parts by mass, di-tert-butyl peroxide was charged at 6 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was 1000 parts by mass of methyl ethyl ketone, and the number of reslurries was changed to 2, by the same procedure as in Production Example 1, a maleic anhydride-modified propylene-ethylene copolymer (PO-8, acid value 25 mg KOH / g-resin, acetone extractable component ratio 1.0 mass%, storage modulus at 25 ° C. 2350 MPa, tensile elongation at break 38% at 25 ° C., weight average molecular weight 60,000, Tm 125 ° C., △H 63 J / g) was obtained as an acid-modified polyolefin.

[0060] Production Example 9 The same procedures as in Production Example 1 were carried out except that the amount of toluene charged was 186 parts by mass, the amount of maleic anhydride charged was 20 parts by mass, the amount of di-tert-butyl peroxide charged was 6 parts by mass, the reaction time was 3 hours, the solvent used for reprecipitation was 1200 parts by mass of methyl ethyl ketone, the solvent used for reslurry was 1200 parts by mass of methyl ethyl ketone, and the number of reslurries was changed to two, thereby obtaining an acid-modified polyolefin, a maleic anhydride-modified propylene-ethylene copolymer (PO-9, acid value 25 mg KOH / g-resin, acetone extractable component ratio 1.2 mass%, storage modulus at 25°C 7 MPa, tensile elongation at break at 25°C 1200%, weight average molecular weight 60,000, no Tm peak, △H0 J / g).

[0061] Manufacturing Example 10 A maleic anhydride-modified propylene-ethylene copolymer (PO-10, acid value 1 mgKOH / g-resin, acetone extractable component ratio 0.1% by mass, storage modulus at 25°C 500 MPa, tensile elongation at break 680% at 25°C) was used as 100 parts by mass, toluene was used as 150 parts by mass, maleic anhydride was used as 0.5 parts by mass, di-tert-butyl peroxide was used as 0.2 parts by mass, the reaction time was 1 hour, the solvent used for reprecipitation was 1000 parts by mass of methyl ethyl ketone, the solvent used for reslurry was 1000 parts by mass of methyl ethyl ketone, and the number of reslurries was changed to 2, by carrying out the same procedure as in Production Example 1, a maleic anhydride-modified propylene-ethylene copolymer (PO-10, acid value 1 mgKOH / g-resin, acetone extractable component ratio 0.1% by mass, storage modulus at 25°C 400 MPa, tensile elongation at break 600% at 25°C, weight average molecular weight 65,000, Tm 71°C, △H 35 J / g) was obtained as an acid-modified polyolefin.

[0062] Manufacturing Example 11 The same procedures as in Production Example 1 were carried out except that the amount of toluene was changed to 150 parts by mass, the amount of maleic anhydride was changed to 50 parts by mass, the amount of di-tert-butyl peroxide was changed to 10 parts by mass, the reaction time was changed to 3 hours, the solvent used for reprecipitation was changed to 700 parts by mass of methyl ethyl ketone, the solvent used for reslurry was changed to 1000 parts by mass of methyl ethyl ketone, and the number of reslurries was changed to 3, to obtain an acid-modified polyolefin, maleic anhydride-modified propylene-ethylene copolymer (PO-11, acid value 55 mg KOH / g-resin, acetone extractable component ratio 1.0 mass%, storage modulus at 25°C 150 MPa, tensile elongation at break 320% at 25°C, weight average molecular weight 30,000, Tm 83°C, △H 25 J / g).

[0063] Manufacturing Example 12 The same procedure as in Production Example 1 was carried out except that the amount of toluene charged was 150 parts by mass, the amount of maleic anhydride charged was 40 parts by mass, the amount of di-tert-butyl peroxide charged was 8 parts by mass, the reaction time was 3 hours, and the number of reslurries was 3 times, to obtain an acid-modified polyolefin, maleic anhydride-modified propylene-ethylene copolymer (PO-12, acid value 46 mg KOH / g-resin, acetone extractable component ratio 4.5 mass%, storage modulus at 25°C 110 MPa, tensile break elongation at 25°C 90%, weight average molecular weight 35,000, Tm 86°C, △H 30 J / g).

[0064] (Preparation of main agent 1) In a 500 ml four-neck flask equipped with a water-cooled reflux condenser and a stirrer, 100 parts by mass of the maleic anhydride modified propylene-ethylene copolymer (PO-1) obtained in Production Example 1, 280 parts by mass of methylcyclohexane, and 120 parts by mass of methyl ethyl ketone were charged, and the mixture was heated to 80°C with stirring, and after stirring was continued for 1 hour, it was cooled to obtain main agent 1. The state of the solution is shown in Table 1.

[0065] (Preparation of base materials 2 to 19) Main agents 2 to 19 were prepared in the same manner as main agent 1, except that the acid-modified polyolefin and organic solvent were changed as shown in Table 1. The blend amounts and solution states are shown in Table 1.

[0066] [Table 1]

[0067] Example 1 An adhesive composition was obtained by mixing 500 parts by mass of the base agent 1 and 1 part by mass of Sumidur (registered trademark) N-3300 as a multifunctional polyisocyanate curing agent (B). The evaluation results of pot life, adhesion, chemical resistance, and moldability are shown in Table 2.

[0068] Examples 2 to 21, Comparative Examples 1 to 3 The base resins 1 to 19 and the curing agents were changed as shown in Tables 2 and 3, and Examples 2 to 21 and Comparative Examples 1 to 3 were carried out in the same manner as in Example 1. The results of the blending amounts, pot life, adhesion, chemical resistance, and moldability are shown in Tables 2 and 3.

[0069] [Table 2]

[0070] [Table 3]

[0071] The curing agents used in Tables 2 and 3 are as follows. <Multifunctional polyisocyanate curing agent (B)> Isocyanurate of hexamethylene diisocyanate: Sumidur (registered trademark) N-3300 (manufactured by Bayer) Biuret form of hexamethylene diisocyanate: Duranate (registered trademark) 24A-100 (manufactured by Asahi Kasei Chemicals Corporation)

[0072] The acid-modified polyolefins, base resins and adhesive compositions obtained as described above were subjected to analysis, measurement and evaluation according to the following methods. Acid Number Measurement The acid value (mgKOH / g-resin) in the present invention refers to the amount of KOH required to neutralize 1g of acid-modified polyolefin (A), and was measured in accordance with the test method of JIS K0070 (1992). Specifically, 1g of acid-modified polyolefin was dissolved in 100g of xylene adjusted to a temperature of 100°C, and then titrated with 0.1mol / L potassium hydroxide ethanol solution [product name "0.1mol / L ethanolic potassium hydroxide solution", manufactured by Wako Pure Chemical Industries, Ltd.] at the same temperature using phenolphthalein as an indicator. At this time, the amount of potassium hydroxide required for titration was converted to mg to calculate the acid value (mgKOH / g).

[0073] Measurement of acetone extractable component ratio The acetone extractable component ratio in the present invention was measured by refluxing with acetone for 2 hours using a Soxhlet extractor. Specifically, 50 g of acid-modified polyolefin (A) was weighed out on a cylindrical filter paper and placed in a Soxhlet extraction tube, and then a flat-bottom flask containing 1100 mL of acetone and a cooling tube were attached and assembled, and the mixture was refluxed in a water bath for 2 hours to perform acetone extraction. Thereafter, the cylindrical filter paper was removed, the acetone extract in the flat-bottom flask was distilled off, and the weight of the residue after further drying under reduced pressure at 100°C for 1 hour was measured, and the value was calculated according to the following formula. Acetone extractable component ratio (mass%) = (extraction residue weight / sample amount) x 100

[0074] Measurement of storage modulus (E') at 25℃ The storage modulus (E') in the present invention was measured in accordance with the test method of JIS K7244-4 (1999). Specifically, it is a value measured using a dynamic viscoelasticity measuring device DVA-200 manufactured by IT Measurement and Control Co., Ltd., at a frequency of 10 Hz while increasing the temperature from -50°C at a rate of 5°C / min.

[0075] Measurement of tensile elongation at break (Eb) at 25℃ The tensile elongation at break (Eb) in the present invention was measured in accordance with the test method of JIS K7161 (2014). Specifically, it is the value of the elongation (%) at break when tensile at a speed of 50 mm / min in an environment of 25° C., using a Tensilon RTM-100 manufactured by Orientec Corporation.

[0076] Measurement of weight average molecular weight (Mw) The weight average molecular weight in the present invention is a value measured using a gel permeation chromatograph Alliance e2695 manufactured by Japan Waters (hereinafter, referred to as GPC, standard substance: polystyrene resin, mobile phase: tetrahydrofuran, column: Shodex KF-806 + KF-803, column temperature: 40°C, flow rate: 1.0 ml / min, detector: photodiode array detector (wavelength 254 nm = ultraviolet light)).

[0077] Melting point and heat of fusion measurement The melting point and heat of fusion in the present invention are values ​​measured using a differential scanning calorimeter (hereinafter, DSC, manufactured by TA Instruments Japan, Q-2000) from the top temperature and area of ​​the melting peak when the material is heated to melt at a rate of 20°C / min, cooled to resinify, and then heated to melt again.

[0078] Evaluation of the base solution state The solution state of main components 1 to 19 was evaluated by measuring the solution viscosity at 25° C. using a Brookfield viscometer TVB-10M (hereinafter also referred to as a B-type viscometer) manufactured by Toki Sangyo Co., Ltd. <Evaluation criteria> ◎ (Excellent for practical use): Less than 500 mPa s ○(Practical): 500 mPa·s or more and less than 1000 mPa·s × (Not practical): Viscosity measurement is not possible due to 1000 mPa s or more or gelation

[0079] Pot life evaluation The pot life refers to the stability of a solution immediately after or after a certain time has elapsed since blending a crosslinking agent or a curing agent into an acid-modified polyolefin. When the pot life is good, the viscosity of the solution increases little and it can be stored for a long time, whereas when the pot life is poor, the viscosity of the solution increases (thickening) and, in severe cases, gelation occurs, making it difficult to apply to a substrate and making it impossible to store for a long time. The pot life of the adhesive compositions obtained in Examples 1 to 21 and Comparative Examples 1 to 3 was evaluated by storing them in an atmosphere of 25° C. and 40° C. for 24 hours and then measuring the solution viscosity at 25° C. using a B-type viscometer. The evaluation results are shown in Tables 2 and 3. <Evaluation criteria> ◎ (Excellent for practical use): Less than 500 mPa s ○(Practical): 500 mPa·s or more and less than 1000 mPa·s × (Not practical): Viscosity measurement is not possible due to 1000 mPa s or more or gelation

[0080] Preparation of a laminate of a metal substrate and a polyolefin resin substrate An aluminum foil (manufactured by Sumikei Aluminum Foil Co., Ltd., 8079-0, thickness 40 μm) was used as the metal substrate, and an unstretched polypropylene film (manufactured by Toyobo Co., Ltd., Pylen (registered trademark) Film CT, thickness 40 μm) (hereinafter also referred to as CPP) was used as the polyolefin resin substrate. The adhesive compositions obtained in Examples 1 to 19 and Comparative Examples 1 to 15 were applied to a metal substrate using a bar coater, with the thickness of the adhesive layer adjusted to 3 μm after drying. The applied surface was dried for 1 minute in a 100°C atmosphere using a hot air dryer, to obtain a metal substrate laminated with an adhesive layer having a thickness of 3 μm. A polyolefin resin substrate was placed on the surface of the adhesive layer, and the laminate was laminated at 0.3 MPa and 1 m / min using a small tabletop test laminator (SA-1010-S) manufactured by Tester Sangyo Co., Ltd. at a lamination temperature of 80°C or 120°C, and aged for 36 hours at 25°C and 50% RH to obtain a laminate.

[0081] The laminate obtained as described above was evaluated by the following methods.

[0082] Adhesion evaluation The laminate was cut into a size of 100 mm × 15 mm, and the adhesiveness was evaluated according to the following criteria by a T-peel test. The evaluation results are shown in Tables 2 to 3.

[0083] <T-peel test> Based on the test method of ASTM-D1876-61, using a tensilon RTM-100 manufactured by Orientec Corporation, the peel strength at a tensile speed of 50 mm / min was measured at 25°C. The peel strength (N / cm) between the metal substrate and the polyolefin resin substrate was taken as the average value of 5 test values.

[0084] <Evaluation criteria> ☆(Particularly excellent in practical use): 8.0 N / cm or more or the CPP breaks (hereinafter, also simply referred to as "material breakage"). Material breakage means that peeling does not occur at the interface between the metal substrate and the CPP, and the metal substrate or the CPP is broken. ◎(Excellent in practical use): 7.5 N / cm or more and less than 8.0 N / cm ○(Practicable): 7.0 N / cm or more and less than 7.5 N / cm ×(Impracticable): Less than 7.0 N / cm

[0085] Chemical resistance evaluation To examine the usability as a packaging material for LiB, the chemical resistance (hereinafter, also referred to as electrolyte resistance) was evaluated by an electrolyte test. The laminate was cut into a size of 100 mm × 15 mm and immersed in an electrolyte [ethylene carbonate / diethyl carbonate / dimethyl carbonate = 1 / 1 / 1 (volume ratio) with lithium hexafluorophosphate added] at 85°C for 1 day. Then, the laminate was taken out, washed with ion-exchanged water, wiped with a paper wiper to remove water, and dried sufficiently to remove moisture, and the chemical resistance was evaluated according to the following criteria by a T-peel test. The evaluation results are shown in Tables 2 to 3.

[0086] <Evaluation criteria> ☆(Particularly excellent in practical use): 8.0 N / cm or more or material breakage ◎(Excellent in practical use): 7.5 N / cm or more and less than 8.0 N / cm ○ (Practical): 7.0N / cm or more and less than 7.5N / cm × (Not practical): Less than 7.0N / cm

[0087] Formability evaluation Similarly, to examine the possibility of using it as a packaging material for LiBs, we evaluated its formability using a deep drawing tester. The laminate was cut into a size of 80×120 mm and cold-formed. Specifically, using an Amada Corporation stretch forming machine (product number: TP-25C-X2), a forming die (female die) having a diameter of 55 mm×35 mm, and a corresponding forming die (male die), cold forming was performed on 10 samples (laminates) at a 25° C. atmosphere with a pressing pressure of 0.4 MPa, changing the forming depth in 0.5 mm increments from a forming depth of 0.5 mm. The deepest forming depth at which no wrinkles, pinholes, or cracks occurred in the aluminum foil in all 10 samples after cold forming was determined as the limit forming depth of the sample. From this limit forming depth, the formability of the battery packaging material was evaluated according to the following criteria. The evaluation results are shown in Tables 3 to 4. <Judgment criteria> ☆ (particularly excellent for practical use): Maximum forming depth 6.0 mm or more ◎ (Excellent for practical use): Limit molding depth is 4.0 mm or more and less than 6.0 mm ○(Practical): Limit forming depth 2.0mm or more, less than 4.0mm ×: Limit forming depth less than 2.0 mm [Industrial Applicability]

[0088] The adhesive composition according to the present invention contains an acid-modified polyolefin, a polyfunctional polyisocyanate curing agent, and an organic solvent, and maintains a good pot life without thickening or gelling even when stored for a long period of time, and can achieve good adhesion between a metal substrate and a polyolefin resin substrate, electrolyte resistance, and moldability. Therefore, a laminate of a polyolefin resin substrate and a metal substrate formed from the adhesive composition of the present invention can be widely used not only in the fields of home appliance outer panels, furniture materials, and building interior materials, but also as packaging materials (pouch form) for lithium batteries used in personal computers, mobile phones, video cameras, etc.

Claims

1. An adhesive composition essentially consisting of an acid-modified polyolefin (A), a multifunctional polyisocyanate curing agent (B), and an organic solvent (C), The acid-modified polyolefin (A) is a propylene-α-olefin copolymer grafted with at least one of an α,β-unsaturated carboxylic acid and an acid anhydride thereof, The acid-modified polyolefin (A) has an acid value of 2 to 50 mg KOH / g-resin and an acetone extractable component ratio of 0.01 to 2 mass%, The polyfunctional polyisocyanate curing agent (B) is contained in an amount of 0.5 to 40 parts by mass per 100 parts by mass of the acid-modified polyolefin (A), The organic solvent (C) is contained in an amount of 110 to 2000 parts by mass relative to 100 parts by mass of the acid-modified polyolefin (A), the organic solvent (C) is a mixed solution of solvent (C1) and solvent (C2), the solvent (C1) is an alicyclic hydrocarbon solvent, the solvent (C2) is a ketone-based solvent, and the mass ratio of solvent (C1):solvent (C2) is 50:50 to 70:30, with the total of the mass ratios being 100; Adhesive composition.

2. 2. The adhesive composition according to claim 1, which is used for bonding a polyolefin resin substrate to a metal substrate.

3. The adhesive composition according to claim 1 or 2, wherein the acid value of the acid-modified polyolefin (A) is 25 to 50 mg KOH / g-resin.

4. A laminate comprising a polyolefin resin substrate and a metal substrate bonded with the adhesive composition according to any one of claims 1 to 3.

5. A packaging material for lithium ion batteries, comprising the laminate according to claim 4 as a constituent member.

Citation Information

Patent Citations

  • Preparation of modified polyolefin having improved adhesiveness

    JP1979099193A

  • adhesive

    JP1990058586A

  • Lithium cell

    JP2001243928A

  • Packaging material for lithium ion battery and manufacturing method thereof

    JP2002216714A

  • Packing material for cell, and cell using the same

    JP2003031188A